Characterization of the genetic diversity of common beans by RAPD markers - Franco, Marília Caixeta; Cassini, Sérvio Túlio Alves; Oliveira, Valter Rodrigues; Tsai, Siu Mui (Pesquisa Agropecuaria Brasileira, 2001)
RAPD (Random Amplified Polymorphic DNA) markers were used to evaluate the genetic diversity among 19 common bean (Phaseolus vulgaris L.) cultivars. Amplifications using 15 decamers primers revealed 108 RAPD loci, 70 of which were polymorphic. The relative genetic distance was estimated using the complement of Jaccard’s coefficient and grouping analyses were derived from UPGMA and Tocher. These two grouping analyses confirmed the broad genetic diversity among the common bean tropical germplasm, which was divided into two main groups. These groups correspond to the Andean (genotypes with medium and large size seeds) and Mesoamerican (genotypes with small seeds) domestication centers. The relative genetic diversity was greater among the Andean cultivars than that of the Mesoamerican cultivars.